Global managers : qualities for effecitve competition - Ali, Abbas J. [Verfasser]; Camp, Robert, C. [Verfasser] (My University, 1996)
"Examines the skills and qualities that are often needed by today's global managers. Describes a study in which 184 international managers raked 13 statements of attributes according to their importance for conducting business affairs. Concludes from the results that qualities pertaining to adaptability, flexibility, and comfortableness in dealing with people from other cultures are often needed. Looks at two factors produced from the results of rotated factor analysis. Labels these factors 'essential qualities' (the attributes required by every manager) and 'supplementary qualities' (the additional attributes required for international assignment). Identifies nine illusions about required managerial qualities which are common in research and practice." (author's abstract; IAB-Doku) ((en)) "Der Artikel präsentiert die Ergebnisse einer Befragung zu nötigen Qualifikationen und Fähigkeiten von international agierenden Managern. Gängige Illusionen von Forschung und Praxis werden dabei aufgedeckt. In der Studie werden 'essentielle Qualitäten', die jeder Manager benötigt, von 'ergänzenden Qualitäten', die bei internationalen Aufgaben nötig werden, unterschieden." (IAB)
Keywords: G 2.1.3 Internationale Arbeitsteilung; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; S 5 Organisationsentwicklung; L 2.3 Methoden; I 2.3.2 Nordamerika; Führungskraft; Qualifikationsanforderung; Auslandstätigkeit; Management; Verhalten; Führungsstil; Pennsylvania; USA; 1992-1992